2019
DOI: 10.1017/s174413311900015x
|View full text |Cite
|
Sign up to set email alerts
|

Getting involved: the extent and impact of patient and public involvement in the Swedish health system

Abstract: Patient and public involvement (PPI) is framed as beneficial for individuals and for the health system. However, little is known about the extent of involvement, or of its impact. Based on data from Sweden, we show that apart from voting in regional elections (76%), more people reported involvement as individual patients (23%) than part of collective activities (5%) or activities relating to a citizen perspective (4%). There was no correlation between how many people participated and the estimated impact – whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The grouping of participants under a collective term is contentious given the lack of homogeneity across patients, public, carers and service users, which fails to account for differences within groups [ 37 ]. The present research accepts the inherent problem in the ‘PPIE’ term, however as per NIHR INVOLVE [ 1 ]the present study considers patients, carers and service users as members of the public.…”
Section: Discussionmentioning
confidence: 99%
“…The grouping of participants under a collective term is contentious given the lack of homogeneity across patients, public, carers and service users, which fails to account for differences within groups [ 37 ]. The present research accepts the inherent problem in the ‘PPIE’ term, however as per NIHR INVOLVE [ 1 ]the present study considers patients, carers and service users as members of the public.…”
Section: Discussionmentioning
confidence: 99%
“… Modified framework for CDs based on Abelson et al (2003) [ 30 ] a Categorising guided by a survey conducted by Demokratiutredningen and SALAR (2015) [ 40 ] b Categorising guided by SALAR ladder of involvement inspired by Arnstein [ 26 ] c Categorising guided by a survey conducted by Gilljam, Karlsson & Sandell (2010) [ 41 ] …”
Section: Methodsmentioning
confidence: 99%
“…It is a national health service system, but highly decentralised. The system is based on a model were the responsibility for healthcare is divided between three levels of government [ 40 ]. The Swedish state is responsible for overall healthcare policy, while responsibility for funding and provision of healthcare lies primarily with the regions (the municipalities are responsible for care for elderly and disabled) [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Opportunities have been made for recovery‐focused care, including development of plans with the input of supported consumers (Reid et al ). There needs to be a consistent approach that is part of everyday routine and not tokenistic (Manias ; Reid et al ) as suggested by Fredriksson and Tritter (), most of the time consultation is more often the norm, than true collaboration.…”
Section: Introductionmentioning
confidence: 99%